<span>Simplifying
4x2 + -24x + 4y2 + 72y = 76
Reorder the terms:
-24x + 4x2 + 72y + 4y2 = 76
Solving
-24x + 4x2 + 72y + 4y2 = 76
Solving for variable 'x'.
Reorder the terms:
-76 + -24x + 4x2 + 72y + 4y2 = 76 + -76
Combine like terms: 76 + -76 = 0
-76 + -24x + 4x2 + 72y + 4y2 = 0
Factor out the Greatest Common Factor (GCF), '4'.
4(-19 + -6x + x2 + 18y + y2) = 0
Ignore the factor 4.
</span><span>Subproblem 1
Set the factor '(-19 + -6x + x2 + 18y + y2)' equal to zero and attempt to solve:
Simplifying
-19 + -6x + x2 + 18y + y2 = 0
Solving
-19 + -6x + x2 + 18y + y2 = 0
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
The solution to this equation could not be determined.</span>
Answer:
44
Step-by-step explanation:
the answer is 44 because 44 is the average and your wondering how i got 44 you add all the numbers up which will be 54 and divide by all the total numbers you have so in that case you hvae 6 numbers so 54 divide by 6 is 44
Answer:
yo dont click that link hes a scammer thats an ip grabber
Answer:
![\dfrac{p^{7} q}{160}](https://tex.z-dn.net/?f=%20%5Cdfrac%7Bp%5E%7B7%7D%20q%7D%7B160%7D%20)
Step-by-step explanation:
![\dfrac{(4p^-4 q)^-2}{10pq^-3} =](https://tex.z-dn.net/?f=%20%5Cdfrac%7B%284p%5E-4%20q%29%5E-2%7D%7B10pq%5E-3%7D%20%3D%20)
![= \dfrac{4^{-2}p^{-4\times (-2)} q^{-2}}{10pq^-3}](https://tex.z-dn.net/?f=%20%3D%20%5Cdfrac%7B4%5E%7B-2%7Dp%5E%7B-4%5Ctimes%20%28-2%29%7D%20q%5E%7B-2%7D%7D%7B10pq%5E-3%7D%20)
![= \dfrac{4^{-2}}{10}p^{8-1} q^{-2-(-3)}](https://tex.z-dn.net/?f=%20%3D%20%5Cdfrac%7B4%5E%7B-2%7D%7D%7B10%7Dp%5E%7B8-1%7D%20q%5E%7B-2-%28-3%29%7D%20)
![= \dfrac{1}{4^2 \times 10}p^{7} q^{-2 + 3}](https://tex.z-dn.net/?f=%20%3D%20%5Cdfrac%7B1%7D%7B4%5E2%20%5Ctimes%2010%7Dp%5E%7B7%7D%20q%5E%7B-2%20%2B%203%7D%20)
![= \dfrac{1}{160}p^{7} q](https://tex.z-dn.net/?f=%20%3D%20%5Cdfrac%7B1%7D%7B160%7Dp%5E%7B7%7D%20q%20)
![= \dfrac{p^{7} q}{160}](https://tex.z-dn.net/?f=%20%3D%20%5Cdfrac%7Bp%5E%7B7%7D%20q%7D%7B160%7D%20)